Dampak Revitalisasi Pasar Sentul terhadap Aktivitas Sosial Ekonomi di Yogyakarta - Nastasya Ristiana Dewi; Kharisma Ayu Budiati; Wahyu Widyastutik; Ana Rostanti; Erni Saharuddin (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2026)
The revitalization of Sentul Market in Yogyakarta, which began in 2023, has changed the social and economic conditions of both traders and buyers. This study aims to determine the impact of the revitalization on the economic conditions of traders and changes in social relations at Sentul Market. This research method used a qualitative approach, with in-depth interviews with eleven informants: six traders and five buyers, as well as direct observation and analysis of relevant documents. The results of this study indicate that although the revitalization provided improvements to physical facilities and a more comfortable market environment, these changes hurt traders due to increased operational costs and a decrease in the number of buyers. Furthermore, the more modern market design reduced the social interactions that previously occurred in traditional markets. Therefore, this study concludes that the revitalization process needs to consider the socio-economic aspects of the market community through appropriate business support, operational cost management, and active participation of traders in the policy planning process.